A STUDY ON DIFFERENT TYPES OF MUTRAKRICCHA VYADHI WITH SPECIAL REFERENCE TO URINE CULTURE EXAMINATION (International Journal of Ayurveda and Pharma Research, 2018)
Mutrakriccha is one of the disease found in about all Ayurvedic Classics where a patient experiences painful and discomfort micturition. Mutrakriccha is of eight types having different signs and symptoms. It can be correlated with dysuria which have two main causes, infective and obstructive, but the most commonest cause is infection. This work has been done to establish any relation of Mutrakriccha vyadhi with urine culture examination and to specify the relationship between any micro-organism with its different types. For the study 100 numbers of patients were clinically diagnosed as Mutrakriccha vyadhi and was investigated for urine culture examination. Finally a conclusion has been drawn showing the relationship of Mutrakriccha vyadhi and its types with pathogenic organism.